Glutamina em dietas para codornas de postura criadas em diferentes ambientes térmicos - Paula, Joyce de (2015)
The experiment was conducted in order to investigate the addition of different levels of glutamine in the diet of Japanese quails posture (Coturnixcoturnix japonica), created in different thermal environments on the characteristics of productive performance, egg quality (Chap.II) and physiological and blood parameters (Chap.III). In Chapter II, we used 210 Japanese quail (Coturnixcoturnix japonica) with 49 days of age and average weight of 160.5±6,45g, distributed in a completely randomized design in subdivided sub plots with three levels of glutamine (0,0; 1,5 and 3,0%), two temperatures (thermoneutral and heat stress), two periods of production lasting 28 days each, five replicates of 7 birds each. The average weight of the birds were assessed variables (g) consumption of feed (g) Egg production (%), egg mass (g) and feed conversion of eggs produced per gram (g/g) and the characteristics quality of eggs Egg weight (g), specific gravity, Haugh units, yolk color (L* and b*), percentage yolk, albumen and shell, albumen pH and shell thickness. Statistical analysis was performed using sub divided portion, applying the Tukey test at 5% significance and application log for egg production and feed conversion variables produced eggs. There were differences (P≤0,05) in the average weight of the birds for rearing and temperature at which the birds had higher weight in the second period and created in thermoneutral temperature. The feed intake showed interaction effect between glutamine and temperature levels, the birds consumed more feed getting both glutamine levels when created in thermoneutral temperature and higher consumption when they received 3,0% glutamine created in heat stress. There were differences (P≤0.05) when evaluated periods of production and glutamine levels for egg production egg mass and feed conversion. With a larger egg production in the second period and when the birds received 1,5 and 3,0% glutamine. For the egg mass and feed conversion, the values were also the best in the second period and the birds fed 3,0% glutamine. For quality characteristics of eggs, diets supplemented with added glutamine have provided improvements to egg weight, pH and percentage of bark, and other variables influenced by the peroxides of production and temperature that birds were created. According to the results it is concluded that the thermoneutral environment and the addition of glutamine in the diet of laying Japanese quail promoted greater improvement in growth performance and quality characteristics of eggs and egg weight, pH, and percentage of shell. Chapter III aimed to evaluate the physiological and blood parameters of laying Japanese quail fed different levels of glutamine and created in different thermal environments. Four periods of production were used lasting 28 days and the statistical design was completely randomized in split sub plots structures, with period in the plot, subplot in temperature and glutamine levels (0,0; 1,5 and 3,0%) allocated to the sub sub plot. In the experiment variables were evaluated: cloacal temperature (TCL), body temperature (TC), total leukocyte count and heterophil: lymphocyte (H:L). For the average TCL, the effect was significant for glutamine and production periods, with lower averages for the birds fed 3,0% glutamine. When evaluated as four periods of production, in which the TCL of the broilers was higher for the last three periods evaluated and lower only in the first xiii production period. In TC evaluations, the significant effect was given to period and temperature, with higher values in the second period and lower in heat stress temperature. Evaluations of total leukocytes significant difference to production periods with higher value only for the fourth study period. For relationship H:L, significant interaction between time periods and temperature with higher values for the second and fourth period to birds raised in thermal stress and for the third time placed in thermoneutral temperature. Based on the results, it is concluded that decreased glutamine levels used TCL and did not affect the blood parameters TC and birds.